Reconsidering the Tartarean Geography of the Iliad: Traces of a Far-Away Tartarus and the Narrative Significance of Localisation. (2022) - Gordon, Joel A.
Abstract: This paper argues for a novel conception of Iliadic Tartarus as a fluid liminal space which includes a superterranean context alongside its (traditionally realised) subterranean localisation. A close reading of Iliad 8.477– 81 reveals traces of superterranean imagery which, alongside the traditional subterranean reading of 8.13– 6 and 14.198– 311, allows for the identification of a fluid, dual-model of Tartarean space within the background of the poem. Further, grounded in recent developments regarding dual localisation within Homeric narrative, this paper explores how localisation can reflect narrative and/or thematic concerns, rather than exclusively denoting spatial-physical realities. Thus, the use of geographical imagery within the three Tartarean passages is examined for its narrative/thematic significance, considering themes such as the hierarchy of the gods and narrative developments such as the relocation of Zeus' positioning within the larger cosmos. The identification of such nuances, in turn, provides a precedent for retaining 'conflicting' or fluid geographical space(s) within the narrative despite the 'contradictions' that they embody.